2021
DOI: 10.3390/sym13101811
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Plant Cell Divisions under Salt Stress

Abstract: Salt stress causes several damaging effects in plant cells. These commonly observed effects are the results of oxidative, osmotic, and toxic stresses. To ensure normal growth and development of tissues, the cellular compartments of multicellular plants have a unique system that provides the specified parameters of growth and differentiation. The cell shape and the direction of division support the steady development of the organism, the habit, and the typical shape of the organs and the whole plant. When divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 100 publications
2
22
0
Order By: Relevance
“…An increasing trend in the amount of lipid bodies in the cytoplasm was observed with the rise of the salinity level ( Figure 5 ). According to Alencar et al [ 17 ] and Baranova et al [ 20 ], our findings can be explained by a salt-induced reduction in lipid reserve mobilization in rocket seedlings. Furthermore, the lack of lipid mobilization in salt-treated plants might be generated by impairment in the peroxisome oil body degradation pathway, especially at the level of the lipase SDP1 activation mechanism.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…An increasing trend in the amount of lipid bodies in the cytoplasm was observed with the rise of the salinity level ( Figure 5 ). According to Alencar et al [ 17 ] and Baranova et al [ 20 ], our findings can be explained by a salt-induced reduction in lipid reserve mobilization in rocket seedlings. Furthermore, the lack of lipid mobilization in salt-treated plants might be generated by impairment in the peroxisome oil body degradation pathway, especially at the level of the lipase SDP1 activation mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, Na + and Cl − ions can negatively interfere with many biochemical processes and can impair lipid reserve mobilization during germination that is a fundamental process for the subsequent seedling development [ 17 , 18 , 19 ]. Thus, ultrastructural changes occurring in lipid mobilization during seedling development in salt stress conditions were evidenced [ 17 , 20 ]. In both studies, salts impaired the normal lipid mobilization of the lipid reservoir, since in salt-affected seedlings, the authors noted a higher occurrence of lipid bodies within the cotyledons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borlu et al [ 44 ] reported considerable differences already at 75 mM NaCl. One of the reasons for the reduction in coleoptile growth under salinity could be combined osmotic-oxidative-toxic stress, which causes a disturbance of cell division, and modification of the structure of cell organelles [ 47 ]. In addition, salt causes the effect of plasmolysis, which is manifested by reduced turgor pressure, which compresses the cell cytoplasm resulting in a disturbance of the growth and shape of the emerging organs.…”
Section: Discussionmentioning
confidence: 99%
“…During cell development, programmed death is characterized by distinct morphological and biochemical changes. The morphological alterations include decreased cell size, increased cytoplasmic density, organelle compression, and chromatin condensation [41].…”
Section: Cytotoxicity By Mtt Cell Proliferation Assaymentioning
confidence: 99%